The Effect of Gender Diversity on Governance Structure on the Sustainability Disclosure Level and Its Impact on the Firm Value (Empirical Study of Public Companies Listed on the Indonesia Stock Exchange for 2016-2020 Period) - Ismaya Aji; Ronny Andesto (Dinasti Publisher, 2022)
This study aims to determine the effect of gender diversity on governance structure on the sustainability disclosure level and its impact on firm value. The research population is public companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. sample determination using the purposive sampling method. Sampling using a purposive sampling method. Based on the criteria, as many as 40 public companies were selected as samples with a total of 200 data. The data analysis method used multiple linear regression analysis with software STATA v.16.0. The test results show that gender diversity in the governance structure of the board of directors, the audit committees, and the board of commissioners has no significant effect on the sustainability disclosure level. Meanwhile, only the gender diversity of the audit committees has a significant effect on firm value, while the gender diversity of the board of directors and the board of commissioners do not affect the firm value. The results also show that the sustainability disclosure level is not able to mediate the effect of gender diversity on the governance structure of the board of directors, the board of commissioners, and the audit committees to the firm value.